Squamous cell carcinoma antigen as an adjunct tumour marker in primary carcinoma of the lung. - Cheah, P.L.; Liam, C.K.; Yap, S.F.; Looi, L.M. (BMJ Publishing Group, 1994)
The findings suggest that CEA is a good general marker for carcinoma, particularly adenocarcinoma. In contrast, squamous cell carcinoma antigen is more specific for squamous carcinoma.